A serial Mediation Model of Depression and Drinking Motives Underlying Problem Drinking Among Hispanic College Women Following Rape - Hirai, Michiyo (Journal of interpersonal violence, 2024)
Problem drinking and depression are common following sexual assault. The current study applied a coping motives model of drinking and examined the association between rape experiences and problem drinking serially mediated by depression symptoms and coping-depression drinking motives among Hispanic college women. A total of 330 college women were classified into a single rape experience (SGL) group (n = 44), a multiple rape experiences (MLT) group (n = 70), and a no sexual assault experience group (n = 221). Participants completed self-report measures online. Serial mediation analyses with multi-categorical predictors found that significantly increased alcohol consumptions in rape survivors compared to individuals with no sexual assault experience were largely explained by the serially connected underlying mechanisms of depression symptoms and coping-depression drinking motives. The prevalence rates of rape experiences in this Hispanic female sample are alarming, suggesting Hispanic college women as a particularly vulnerable group for rape. The current results contribute to a greater understanding of the effects of rape experiences on behavioral and emotional outcomes among young Hispanic women who have been underrepresented in sexual victimization research. The findings emphasize the importance of assessing depression symptoms and coping-depression drinking motives in Hispanic rape survivors to reduce risks for hazardous drinking behavior.